Digital Transformation in Social Entrepreneurship: Driving Sustainable Economic Development in Rural Areas - Muhamad, Lili Fadli; Kusuma, Aditya Putra (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2024)
Rural areas often face significant economic challenges, including limited access to resources and limited economic opportunities. Social entrepreneurship has proven to be an effective model for enhancing community welfare through innovative and sustainable solutions. This research aims to analyze how digital transformation can be applied in social entrepreneurship in rural areas. The research method employed is a literature review with a qualitative approach focused on community engagement, with descriptive analysis. In this regard, the researcher will conduct descriptive analysis of the content of 25 carefully selected articles through Google Scholar selection for the period 2003-2024. The study findings indicate that digital transformation in social entrepreneurship in rural areas promises fundamental changes in the economic landscape, bringing new hope for sustainable economic growth. By leveraging information and communication technology, social entrepreneurs can overcome geographical challenges and enhance market access and resources. However, to optimize the potential of this transformation, comprehensive support from various stakeholders and attention to several key aspects such as digital infrastructure, education and training, empowerment of local entrepreneurs, product innovation and business model, stakeholder collaboration, as well as monitoring and evaluation are required.